Crafting identity : the development of professional fine craft in Canada - Alfoldy, Sandra (McGill-Queen's University Press, 2005)
Pioneering professional craft in Canada -- Aileen Osborn Webb and the American Craft Council: establishing a professional craft ideology -- 1967: a contennial year of crafts in Canada and a leadership role for native crafts -- Professional education, professional aesthetics -- The dis/unity of craft: in praise of hands, Toronto, 1974 -- The professional ascendancy of the crafts.